Reinstatement of Perinereis bairdii (Webster, 1884) and description of P. websteri sp. nov. from Bermuda, including the reproductive morphology of two Atlantic Perinereis species (Annelida: Errantia: Phyllodocida) - Conde-Vela, Víctor Manuel (European Journal of Taxonomy, 2022)
Perinereis anderssoni Kinberg, 1865 originally described from Brazil has been attributed with a wide distribution on the American Atlantic coasts, ranging from Brazil to Bermuda, due to the synonymy of Nereis bairdii Webster, 1884 and Nereis (Perinereis) melanocephala McIntosh, 1885. In this paper, the synonymy of Nereis bairdii with Perinereis anderssoni is rejected based on a re-examination of the syntypes of N. bairdii which are found to contain two species requiring designation of a lectotype and paralectotypes here redescribed as Perinereis bairdii (Webster, 1884) and the remaining specimens are here described as Perinereis websteri sp. nov. The synonymy of Nereis (Perinereis) melanocephala with P. anderssoni is rejected and the synonymy with P. bairdii proposed by previous authors is accepted here. A description of P. anderssoni, a redescription of P. floridana, and a description of the males of P. cariboea with additional material are provided for comparison. A key to identifying all Atlantic Perinereis species is also included.